FREQUENCY RESPONSE OF A PRE-STRESSED METAL ELASTIC PLATE UNDER COMPRESSIBLE VISCOUS FLUID LOADING - Akbarov, S. D.; Ismailov, M. I. (MINISTRY COMMUNICATIONS & HIGH TECHNOLOGIES REPUBLIC AZERBAIJAN, 2016)
The forced vibration of the system consisting of a pre-stressed metal plate made of a nonlinear elastic material and a half-plane filled by a barotropic compressible Newtonian viscous fluid is considered. It is assumed that this forced vibration is caused by the lineal-located time harmonic force acting on the free face plane of the plate. The motion of the pre-stressed plate is written by utilizing the linearized exact equations of the theory of elastic waves in initially stressed bodies, but the motion of the compressible viscous fluid is described by the linearized Navier-Stokes equations. It is assumed that the elasticity relations of the plate material are written through the Murnaghan potential.
Keywords: Compressible Viscous Fluid; Metal Elastic Plate; Initial Stress; Frequency Response; Forced Vibration; STRESS-FIELD; HALF-SPACE; VIBRATIONS; WAVES; LAYER; PROPAGATION; VISCOSITY; SYSTEM; Mathematics